The Phenomenon of Health Cadre Performance Motivation in Communities in The Homeland of The Baduy - Tatiana Siregar; Ritanti Ritanti; Indah Permatasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACTThis study explores the phenomena that motivate Baduy Health Cadres to carry out their societal roles. This study uses a qualitative method of the Transcendental Phenomenology type. The results of the survey obtained seven main themes, namely: Increasing knowledge, Concern for residents, Self-actualization, Support for residents to have MCK, Cultural preservation, Compensation, and Cadre Training. In conclusion, the seven themes motivate Health Cadres to carry out their roles. Keywords: Self-Actualization, Health Cadres, Motivation, Compensation, Baduy Tribe